Controls on decadal, annual, and seasonal concentration‐discharge relationships in the Sleepers River Research Watershed, Vermont, northeastern United States. Issue 3 (28th March 2022) - Porter, Veronica M.; Shanley, James B.; Sebestyen, Stephen D.; Liu, Fengjing
Abstract: Past studies on concentration‐discharge ( C‐Q ) relationships have focused on short‐term or low‐temporal resolution data. While advancing understanding of catchment processes, these studies provided limited insight on catchment response over time or to climate change. Using 15 solutes from 1992 to 2015 at Sleepers River Research Watershed, Vermont, we compared C‐Q relationships over decades, years, and seasons to elucidate controls on stream chemical variation. We applied end‐member mixing analysis (EMMA) to identify solute sources and flow path routing. EMMA identified three end‐members: near‐surface runoff (NSR), riparian groundwater, and hillslope hollow groundwater. Shifting mixing proportions of these end‐members accounted for the temporal variability of conservative (no chemical reaction en route from source to stream) solutes in streamflow. For example, an increase in NSR fraction, typical of high flow, caused flushing (increased concentrations) of NO3 −, DOC, Al, and Fe, which were greatest in NSR, dilution of specific conductance and base cation, SO4 2−, Si, Sr, Ba, and Mn concentrations, which were greatest in the two groundwater end‐members. This behaviour is reflected in the b ‐coefficient of the C‐Q relation ( C = aQ b ), which indicates the strength of dilution ( b < −0.1) and flushing ( b > 0.1) effects. For conservative solutes, the b ‐coefficient decreased significantly ( p < 0.01) with an increase in the groundwater to NSR concentration ratio. Solutes that are conservative and have relatively constant concentrations in end‐members over time showed consistent annual C‐Q patterns over years and decades. Furthermore, the strength of dilution or flushing was stronger during the snowmelt period, when the NSR fraction peaked, than during the dormant and growing seasons. With shorter snowmelt periods and snow to rain shifts, the flushing or dilution power of snowmelt runoff will weaken and alter catchment response to climate change. These insights provide more tools for the interpretation of catchment processes and responses to climate change. Abstract : The concentration‐discharge ( C‐Q ) relationship in streamflow is determined by distinctiveness of solute concentrations and the fractions between shallow and deeper flowpaths. Conservative solutes with distinct and relatively constant concentrations in end‐members showed stronger and consistent annual C‐Q patterns over years and with decadal timescale. The b ‐coefficient is highly correlated with the difference of solute concentrations between groundwater and near‐surface runoff (NSR) and does not necessarily have a magnitude close to 1 for conservative mixing of streamflow chemistry.